2001
DOI: 10.1177/c10n1r7
|View full text |Cite
|
Sign up to set email alerts
|

Referring Abused Women: Does Police Assistance Decrease Abuse?

Abstract: To evaluate if abused women's use of the police reduced further violence experienced, 90 abused women were interviewed at a large urban police department and followed for 6 months. Frequency and severity of violence as well as danger of homicide were measured before and at 3 and 6 months after women sought police help. Women seeking police help had significantly reduced threats of abuse (F = 124.62, df = 2,81; p < .0005), actual abuse (F = 90.11, df = 2,81; p < .0005), and danger of being killed (F = 188.69, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Outside of the replication studies, research has continued to show conflicting findings as to arrest efficacy; however some studies have found positive effect (e.g., Langan & Innes, 1986;Wiist & McFarlane, 1998;Willson, McFarlane, Lemmey & Malecha, 2001). In a study of 90 abused women, McFarlane and colleagues (2000) found a less positive outcome, with no change in future violence based on arrest of the offender.…”
Section: Police Response To Violence Against Womenmentioning
confidence: 99%
“…Outside of the replication studies, research has continued to show conflicting findings as to arrest efficacy; however some studies have found positive effect (e.g., Langan & Innes, 1986;Wiist & McFarlane, 1998;Willson, McFarlane, Lemmey & Malecha, 2001). In a study of 90 abused women, McFarlane and colleagues (2000) found a less positive outcome, with no change in future violence based on arrest of the offender.…”
Section: Police Response To Violence Against Womenmentioning
confidence: 99%
“…There is some evidence that abused women who involve the police have lower rates of violence than those who do not, though it is not clear whether this is due solely to the actions of the police. 47 There is randomised controlled trial evidence that advocacy services have a role in reducing levels of violence, though whether this American evidence applies to a UK population is unclear. 48 There is also cohort evidence that community protection orders in the US are associated with lower rates of abuse, although again the external validity of a study conducted in the US to British practice is limited.…”
Section: Improving Detection Of Domestic Violencementioning
confidence: 99%
“…The clinician along with local domestic violence advocates can describe the expected police action in a particular community. Police involvement has been associated with decreased severity and frequency of abuse, when assessed 6 months after initiation of police involvement (81).…”
Section: Appendix a Domestic Violence Intervention Approachesmentioning
confidence: 99%